Initiating patient discussions about oocyte cryopreservation: Attitudes of obstetrics and gynaecology resident physicians. (August 2018) - Peterson, B.; Gordon, C.; Boehm, J.K.; Inhorn, M.C.; Patrizio, P.
Abstract: This study examined the attitudes of obstetrics and gynaecology (OB/GYN) resident physicians to initiating patient discussions regarding medical and elective oocyte cryopreservation (OC). The study used a cross-sectional online survey of OB/GYN medical residents in the USA, sampled from residency programmes approved by the American Council for Graduate Medical Education. In total, 208 medical residents, distributed evenly between postgraduate years 1–4, participated in the study. Residents' fertility knowledge and attitudes to initiating discussions about OC were gathered. Forty percent ( n  = 83) believed that OB/GYN residents should initiate discussions about OC with patients (initiators), while 60% ( n  = 125) did not (non-initiators). Initiators were less likely to overestimate the age at which a woman's fertility begins to decline, and were more likely to believe that discussions about OC and age-related fertility decline should take place during a well-woman annual examination. Initiators and non-initiators did not differ in their attitudes towards discussing OC with patients undergoing cancer treatments; however, initiators were significantly more likely to discuss elective OC with patients who were currently unpartnered or who wished to delay childbearing to pursue a career. Given the increasing age of childbearing among women, and the fact that women prefer to receive reproductive information from their healthcare providers, it is critical that such topics are discussed in consultations to assist patients in making more informed reproductive decisions. Further research is needed to assess the existing barriers to these discussions from both physician and patient perspectives.